2020
DOI: 10.1111/1462-2920.15332
|View full text |Cite
|
Sign up to set email alerts
|

The anaerobic survival mechanism of Schizophyllum commune20R‐7‐F01, isolated from deep sediment 2 km below the seafloor

Abstract: Summary Fungi dominated the eukaryotic group in the anaerobic sedimentary environment below the ocean floor where they play an essential ecological role. However, the adaptive mechanism of fungi to these anaerobic environments is still unclear. Here, we reported the anaerobic adaptive mechanism of Schizophyllum commune 20R‐7‐F01, isolated from deep coal‐bearing sediment down to ~2 km below the seafloor, through biochemical, metabolomic and transcriptome analyses. The fungus grows well, but the morphology chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Fungi take part in degradation of hydrocarbons in soils and sediments, including aromatic compounds [ 103 – 105 ]. Physiologically versatile fungi persist in the deep subsurface biosphere, and have been cultivated from coal-bearing deep subsurface sediments at 2 km depth [ 106 , 107 ]. Over 100 fungal genera are known to play important roles in biodegradation [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi take part in degradation of hydrocarbons in soils and sediments, including aromatic compounds [ 103 – 105 ]. Physiologically versatile fungi persist in the deep subsurface biosphere, and have been cultivated from coal-bearing deep subsurface sediments at 2 km depth [ 106 , 107 ]. Over 100 fungal genera are known to play important roles in biodegradation [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCAAs are essential amino acids and are synthesized as building blocks of protein; however, the increased production of these AAs under low oxygen conditions is considered to be another strategy of fungi to cope with oxygen deficiency (Shimizu et al ., 2010; Zain ul Arifeen et al ., 2021). As a nutrient and signalling molecules in protein formation and metabolic homeostasis, BCAAs play key roles in the growth, development, and reproduction of fungi (Neinast et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Ile shows an important effect on appressorium formation, hyphae growth, and morphogenesis of pathogenic fungi Fusarium graminearum and Magnaporthe oryzae (Liu et al ., 2014; Du et al ., 2014), and Leu is taught to be crucial for the growth and conidia formation of various fungi (Tang et al ., 2018). Our findings also suggest that sub‐seafloor fungus S. commune uses BCAAs not only to regenerate ATPs (Zain ul Arifeen et al ., 2021) but also to support growth as a nutrient (Fig. 2A) under the anoxic conditions, which may contribute to the diversity and richness of fungus in the sub‐marine environment with extremely deficient in energy resources and relatively high necromass (peptide and amino acids from the dead microbial cells) over geological times (Lomstein et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This number of marine fungi is low in comparison to the number of terrestrial fungi, but marine fungi are predominantly saprobes and rely on the abundant organic matter available in coastal environments [ 5 ]. In the sea, a number of factors affects fungi growth, such as salinity, temperature [ 6 ], hydrostatic pressure in the deep-sea [ 7 ] and the anoxic conditions of the sediment [ 8 ]. Light may affect reproductive behavior of marine fungi [ 9 ].…”
Section: Introductionmentioning
confidence: 99%